Dhulikhel Hospital Checklist Protocol for Temporal Bone Computed Tomography Scan Analysis: How We Do It? - Shrestha, B. L.; KC, A.K.; Karmacharya, S. (Kathmandu University Medical Journal, 2022)
The temporal bone is very complicated anatomical structure. Any disease process within this structure mandates thorough anatomical knowledge of the corresponding structure. The High resolution computed tomography (HRCT) temporal bone is the best way to look inside this complex bone. The importance of knowledge about how to read and look inside the CT scan temporal bone lead us develop the Dhulikhel Hospital Check list protocol. This protocol will help aspiring otologist and otolaryngologist to read and know details about the underlying structures.